Review Analysis of Cyber Security in Healthcare System: A Systematic Approach of Modern Development (International Journal of Innovative Research in Computer Science & Technology, 2023)
The healthcare industry provides medical  devices such as pharmaceuticals. The third-party vendor can  also pose a risk to the organization. Cyber security if they are  not properly vetted and do not have adequate security  measures in place. These will help to mitigate and other  cyber security risks, healthcare organizations should  implement a range of security measures. Regular security  assessments in healthcare organizations should conduct a  regular security assessment to identify vulnerable in their  systems and network. Distributed dental or services attacks  where criminals overload the healthcare system. Health care  system servers with traffic, causing them to crash and  preventive. Lag mate users from accessing the system's  network, stealing data, and causing damage to the  system. Ensure that these tools are updated regularly to  protect against the latest threats. Regularly check the backup  data and critical data and store them in a secure location.  Monitoring network activity to detect and respond to any  potential security incidents conduct regularly.
Keywords: Cyber; Data; Healthcare Security; Malware; Systematic; Technology